CSI feedback algorithm based on RM-Net for massive MIMO systems in high-speed mobile environment - Yong LIAO; Shiyi WANG (Tongxin xuebao)
Aiming at the complex and changeable channel characteristics in high-speed mobile environment, and the influence of additive noise and nonlinear effects, a residual mixing network (RM-Net) for massive MIMO CSI feedback was proposed.By learning the spatial structure and temporal correlation of high-speed mobile channel, the network was able to remove massive MIMO channel noise, and the CSI compression rate and recovery quality could be significantly improved.System simulation results show that RM-Net can eliminate the influence of additive noise in high-speed mobile scenarios, learn and adapt to the channel characteristics of sparse and double-selective fading channels, and still has good performance under the conditions of high compression rate and low signal-to-noise ratio.The proposed algorithm performance is much better than other CS-based and DL-based CSI feedback algorithms.